Однородные решения задачи о равновесии анизотропных пластин с одной плоскостью упругой симметрии - Шевченко, В.П.; Алтухов, Е.В.; Нескородев, Р.Н. (Видавничий дім "Академперіодика" НАН України, 2008)
We have constructed homogeneous solutions of the equations of elastic equilibrium for a plate, on the flat edges of which the normal component of a vector of displacements and tangential stresses are equal to zero. An explicit analytic solution of the problem on the stressed state of a layer with elliptic hole in case of the action of a load that is constant over thickness is obtained.